Manutenção da qualidade do guacamole elaborado com abacate ‘Hass’ submetido a hidrotermia - Daiuto, Érica Regina [UNESP]; Vieites, Rogério Lopes [UNESP]; Russo, Viviane Citadini [UNESP]; Fumes, Joana Giffoni Figueiredo [UNESP]; Simon, Juliana Wagner [UNESP] (My University, 2010)
The aim of this work was to verify the maintenance of quality and acceptability guacamole conserved by the cold and elaborated with fruits submitted the thermal treatment. After selection, the fruits of the Hass variety, ripened were submitted to bath‐water at 45ºC for 5, 10, 15 and 20 minutes. To follow the guacamole it was elaborated with the fruits submitted the thermal treatment,  constituting 5 treatments with the control whose fruits were not treated. The product was conditioned in polyethylene+nylon packages and submitted to freezing to ‐18ºC, where they stayed stored. The evaluations went to the 0, 30, 60 and 90 days in the frozen samples and to the 3 and 7 days in samples maintained under refrigeration after the 90 days frozen. The evaluation parameters were the color, pH, acidity, polyphenol oxidase activity in the pulp and guacamole. The product acceptability was evaluated by sensorial analysis just for the guacamole elaborated with fruits of the control treatment and that submitted to thermal treatment for 10 minutes. It was also verified the product microbiological stability. It was observed a reduction in the color parameters values in pulp fruit recently cut in relation to the guacamole, but without to affect the product aspect. The darkening index values varied from 52,37 to 86,42% of the beginning to the end of the experiment. With the storage there was tendency of  the darkening samples for all of the treatments. The pH values were smaller in the guacamole in relation to pulp and they stayed stable during freezing storage. The control treatment was the more stable in the maintenance of the acidity values during the storage. The polyphenol oxidase activity was smaller in the guacamole in relation to the pulp, in function of the used formulation, and the smallest values were found for the control   treatment. In general the product was well accept and without difference among the treatments. The product was microbiologically stable in the analyzed period. The results indicate that the thermal treatment in the fruits, previous to the guacamole elaboration, it can maintain the quality of the guacamole conserved by the cold, however it is not effective to improve the product if compared to the control treatment.

O objetivo desta pesquisa foi avaliar manutenção da qualidade e aceitabilidade do guacamole conservado pelo frio e elaborado com frutos submetidos a hidrotermia. Após seleção, os frutos da variedade Hass, amadurecidos foram submetidos a banho‐maria à 45ºC por 5, 10, 15 e 20 minutos. A seguir foi elaborado o guacamole com os frutos submetidos a hidrotermia, totalizando 5 tratamentos com a testemunha cujos frutos não foram tratados térmicamente. O produto foi acondicionado em embalagens de nylon+polietileno e submetido a congelamento em freezer doméstico a ‐18ºC, onde permaneceram armazenadas. As avaliações foram aos 0, 30, 60 e 90 dias nas amostras congeladas e aos 3 e 7 dias em amostras mantidas sob refrigeração após os 90 dias congeladas. Os parâmetros de avaliação foram a cor, pH, acidez, atividade da polifenoloxidase realizados na polpa e no guacamole. A aceitabilidade do produto foi avaliado por análise sensorial apenas para o guacamole elaborado com frutos do tratamento testemunha e os submetidos a hidrotermia por 10 minutos. Foi verificada também a estabilidade microbiológica deste produto. Observou‐se uma redução nos valores dos parâmetros de cor da polpa do fruto recém cortado em relação ao guacamole, mas sem prejudicar o aspecto do produto. Os valores de índice de escurecimento variaram de 52,37 a 86,42% do início ao final do experimento. Com o armazenamento houve tendência de escurecimento das amostras para todos os tratamentos. Os valores de pH foram menores no guacamole em relação a polpa e se mantiveram estáveis durante o armazenamento pelo frio. O tratamento testemunha foi o mais estável na manutenção dos valores de acidez durante o armazenamento. A atividade da polifenoloxidase foi menor no guacamole em relação à polpa, devido a formulação utilizada, e os menores valores foram encontrados para o tratamento testemunha. De modo geral o produto foi bem aceito e sem diferença entre os tratamentos. O produto foi microbiologicamente estável no período analisado. Os resultados indicam que o tratamento térmico nos frutos, prévio à elaboração do guacamole, pode manter a qualidade do guacamole conservado pelo frio, no entanto não é eficaz para melhorar o produto se comparado ao tratamento testemunha.
Maintenance of the guacamole quality elaborated with avocado 'Hass' submitted thermal treatment
Keywords: Persea americana Mill; Processing; Fresh cut; Persea americana Mill; Processamento; Minimamente processado